Phytochemical and Biological Potential of Indrayan: An Overview - Kumar, Vikash; Rathee, Permender; Kohli, Kanchan; Chaudhary, Hema; Rathee, Sushila (Pharmacognosy Reviews)
Medicinal plants play an imperative role in the management of various diseases especially in the developing countries where resources are meager. Indrayan (Citrullus Colocynthis Schard.) has been reported as folk medicine in various countries. It has been traditionally used as an abortifacient and to treat constipation, oedema, bacterial infections, cancer and diabetes. The principal constituents of colocynth include alkaloids, triterpenoids, glycosides and resins which are mainly responsible for its biological activities. Considering the extensive interest and recent progress on the structural and biological activity of active constituents, the present review systematically focuses on the structures and biological activity of the plant.
Keywords: Medicinal plants; Folk Medicine; Citrullus Colocynthis; Cucurbitaceae; Activity